Life history, diet and distribution of three grenadier species in South Africa - Baur, Niclas (Department of Biological Sciences, 2025)
The Macrouridae are a diverse and varied family of deep-sea fishes which, barring a few commercially exploited species, have not received sufficient scientific attention. A lack of basic life history data in the species Coelorinchus braueri, Coelorinchus simorhynchus, and Malacocephalus laevis prevents assessments of their stocks and their vulnerability to bycatch mortality in the South African offshore trawl fishery. To remedy this, more than 500 specimens across the three species were collected over the course of a year from the South African west and south coasts, with sampling occurring every 1–3 months. These were measured and dissected to provide data on distribution, morphometrics, biometrics, growth, age structure, diet, reproduction, and parasites. A von Bertalanffy regression was fitted to Coelorinchus braueri growth data, and length-weight regressions were fitted for all three species. Stomach dissections were used to identify prey taxa and calculate their index of relative importance, reproductive seasonality was assessed, and the ovarian organisation of Coelorinchus simorhynchus and Malacocephalus laevis were described. Macroscopic and histological images of female and male gonads are presented here for the first time. These were used to measure sexual development phase and investigate reproductive seasonality. The life history data were interpreted in the context of the deep-sea habitat occupied by these species and the limitations inherent in studying trawl-captured deep-sea fishes and macrourids in general. Comparisons between information revealed here and previous studies on grenadiers were made where possible. Morphometric estimations for total length (TL) from pre-anal fin length (PAFL) were determined to be as follows: TL = 2.22 * PAFL + 56.7 (C. braueri), TL = 2.84* PAFL + 66.0 (C. simorhynchus), and TL = 3.73 * PAFL + 136.0 (M. laevis). In all species females were larger than males. No clear patterns of PAFL or average mass with depth were found. Sex ratios did not consistently vary with depth, but were different on the west and south coasts. Gonado-somatic index (GSI) was typically less than 1% in males and between 2% and 8% in females. No evidence for strong reproductive seasonality was found. C. braueri showed isometric growth (Mass = 8.36x10-5 * PAFL2.97), and had a PAFL50 of 107 (females) and 89 mm (males). A von Bertalanffy regression for this species was estimated as PAFLt = 169.13*(1 – e -0.10*(t - (-1.73) ) ), and the maximum observed age of 17 years was roughly in line with what is known from this genus. C. braueri preyed primarily on small crustaceans and teleost fish. The sex ratio in this species was biased towards females, with mean female GSI of 3.2%. The copepod Sphyrion quadricornis was found on this species, along with unidentified chondracanthid copepods in the gill chamber. C. simorhynchus showed isometric growth (Mass = 1.12x10-4 * PAFL3.08) and had a PAFL50 of 71 (females) and 32 mm (males). C. simorhynchus preyed primarily on a mix of crustaceans, ophiuroids and teleosts. The sex ratio in this species was biased towards females, with mean female GSI of 3.7%. The ovaries in this species were categorised as asynchronous. The copepod Sphyrion quadricornis was found on this species. M. laevis showed hypoallometric growth (Mass = 2.09x10-3 * PAFL2.59). M. laevis preyed primarily on teleosts and cephalopods, as well as some large prawns. The sex ratio in this species was roughly equal, with mean female GSI of 2.6%. The ovaries in this species were categorised as group synchronous. Unidentified chondracanthid copepod parasites were found in the gill chamber of this species. External parasites were identified where possible. The parasite loads and their locations on the specimens were described. Both Coelorinchus species were found to be parasitised externally by copepod Sphyrion quadricornis, while C. braueri and M. laevis were beset by unknown chondracanthid gill copepods. It is evident that much work remains to be done before these species, and other less wellresearched macrourids may be incorporated into ecosystem and fisheries models or before their stocks and vulnerability may be assessed. Furthermore, it is clear that these species of grenadiers differ in many of their life history characteristics. Future models and fisheries policies must not treat grenadiers interchangeably, but rather consider them on a species-byspecies basis where possible.